2001
DOI: 10.1111/j.1572-0241.2001.03753.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Celiac Disease Autoantibodies in Patients With Systemic Lupus Erythematosus

Abstract: The presence of false positive antigliadin antibodies in patients with systemic lupus erythematosus is common. Despite shared human lymphocyte antigen loci there does not seem to be an association between celiac disease and systemic lupus erythematosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…[23] SLE association to CD is likely rare as one study did not find hidden cases in 103 patients with SLE. [24] A more recent study from Northern Ireland did not reveal clinical evidence of SLE among a cohort of 60 celiac disease patients. [25] While gastrointestinal manifestations of SLE are common in both adults and children, [26][27][28] CD is relatively rare among this patient population but should be considered in the setting of malabsorption symptoms.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…[23] SLE association to CD is likely rare as one study did not find hidden cases in 103 patients with SLE. [24] A more recent study from Northern Ireland did not reveal clinical evidence of SLE among a cohort of 60 celiac disease patients. [25] While gastrointestinal manifestations of SLE are common in both adults and children, [26][27][28] CD is relatively rare among this patient population but should be considered in the setting of malabsorption symptoms.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…The increased presence of antigliadin antibodies in patients with SLE has been considered to represent false positivity, which is consistent with the presence of false positive autoantibodies for numerous other conditions in patients with SLE. 15 One study by Lerner et al 38 observed that in a group of patients with CD, 23% had anti-dsDNA and 14% had anticardiolipin antibodies. However, a study by Caglar et al 39 found no significant differences in the frequency of a number of anticytoplasmic and antinuclear antibodies between patients with CD and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…1 In children ages 2.5 to 15 years this prevalence has been reported as between 0.3% and 1.3%. [2][3][4] Studies have shown an association between CD and numerous autoimmune and rheumatic conditions including rheumatoid arthritis, 5,6 juvenile idiopathic arthritis (JIA), [7][8][9][10] autoimmune thyroiditis, [10][11][12] autoimmune thrombocytopenic purpura, hemolytic anemia, 6 vasculitis, 5,6 polymyositis and dermatomyositis, 13,14 systemic lupus erythematosus (SLE), 5,6,15,16 scleroderma, 5,6 mixed connective tissue disease, 5 diabetes mellitus, [17][18][19][20][21][22] Sjögren syndrome, 6,10,23,24 and dermatitis herpetiformis. 24 Among the connective tissue disorders, only Sjögren syndrome appears to share the HLA DQ2/DQ8 haplotype with CD.…”
Section: What This Study Addsmentioning
confidence: 99%
“…3 Those with a lack of speci¢city for coeliac disease will result in an inappropriately high number of referrals for duodenal biopsy. 4,5 Similarly, any test with a low sensitivity will miss an unacceptably large number of cases.…”
Section: Introductionmentioning
confidence: 99%